Efektivitas Penerapan Sistem PTSP Pada Mal Pelayanan Publik Di Kabupaten Sumenep Jawa Timur - Ali, Subhan Maruf; Radjikan, Radjikan; Hartono, Supri (JPAP: Jurnal Penelitian Administrasi Publik, 2023)
The achievement of a predetermined or planned goal is known as effectiveness. The implementation of the One-Stop Integrated Service System at the Sumenep Regency Public Service Mall, East Java, is still relatively new. In fact, this system still needs significant improvement. The purpose of this study was to find out the application of the One Stop Integrated Service System at Public Service Malls in Sumenep Regency, East Java and to find out how far the Effectiveness of the Implementation of One Stop Integrated Services at Public Service Malls in Sumenep Regency, East Java. The research method used is descriptive qualitative research. Data obtained through observation techniques, interviews, documentation and literature study. The theory used is the theory of effectiveness measurement according to Kettner, Moroney, and Martin including effort, cost efficiency, result, cost effectiveness, impact. The data analysis technique used was proposed by Miles & Huberman namely data collection, data reduction or data simplification, data presentation, and conclusion drawing. The research results obtained are that the application of a One-Stop Integrated Service System at Public Service Malls in Sumenep Regency, East Java is in accordance with the objectives of establishing a Public Service Mall, the Implementation of a One-Stop Integrated Service System at Public Service Malls in Sumenep Regency, East Java is already effective. The advice given is that it is hoped that MPP will optimize services more, not attract additional fees beyond the provision of service fees, be consistent with their attitudes and duties in providing services, consistently focus on the existing budget for the implementation of licensing and non-licensing services, and hope that the positive impact will be felt by the community Service users are evenly distributed throughout the archipelago.